PENGEMBANGAN GAME EDUKASI BERBASIS ANDROID SEBAGAI MEDIA PEMBELAJARAN SISWA SD - Juhri, Deny Apriyani; Irawan, Handika; Shalsabila, Shofi; Setyaningrum, Dinda (JURNAL LENTERA [PENDIDIKAN PUSAT PENELITIAN LPPM UM METRO], 2022)
This research develops a product in the form of an Android-based educational game media as a student learning medium in thematic subjects for class III elementary school students. This study used the Research and Development (R&D) research method with the Luther development model consisting of 6 stages. Data collection techniques through questionnaires, and documentation. The results  of  this  study  were:  1)  Android-based  educational  game  products  as  learning  media,  2) feasibility  assessments  carried  out  by  experts,  based  on  the  validation  results  of  media  experts obtained a percentage of 78.88% or feasible, material experts obtained a percentage of 83.33%. meets the very feasible category, 3) the practicality of the media is assessed based on the results of the user response questionnaire analysis. In the student response test at UPT SD N 2 Banyuwangi obtained a percentage of 91.66%, while the educator's response obtained a percentage of 87.75%. While the implementation of the trial at UPT SD N 1 South Pandansari in the response of students obtained a percentage of 88.96% and the response of educators was 80%, the product was very practical to use.